Dual wavelength optical duobinary modulation using GaAs–AlGaAs microring resonator - Amiri, Iraj Sadegh; Zakaria, Rozalina; Anwar, Toni; Bahadoran, Mahdi; Vigneswaran, Dhasarathan; Yupapin, Preecha Promphan (Elsevier, 2018)
In this article, optical duobinary modulation technique has been used for modulating the dual-wavelength optical signal generated by the microring resonator system. The optical signals are de-multiplexed to two different optical signals with center wavelength of 1540 and 1545 nm afterward, these are modulated and transmitted over an optical fiber communication system, where the high performance of the transmitted signals is obtained. The NRZ binary signals are used to modulate the optical signals. The high-quality factor and performance of the system has been investigated by applying an optimization through the system parameters, where significant improvement could be obtained and highest quality factor of 32.871 shows the successful transmission. The second wavelength of the dual-wavelength has undergone the same modulation technique and has experienced the optical transmission after the system optimization has been performed, where the quality factor for the received optical signal at 1545 nm center wavelength is 39.282. These results show the introduced modulation technique is suitable to apply for the optical signals generated by the microring resonators.